1998
DOI: 10.1002/(sici)1097-0061(199811)14:15<1373::aid-yea332>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the peroxisomal acyl CoA oxidaseACO3 gene from the alkane-utilizing yeastYarrowia lipolytica

Abstract: The ACO3 gene, which encodes one of the acyl‐CoA oxidase isoenzymes, was isolated from the alkane‐utilizing yeast Yarrowia lipolytica as a 10 kb genomic fragment. It was sequenced and found to encode a 701‐amino acid protein very similar to other ACOs, 67·5% identical to Y. lipolytica Aco1p and about 40% identical to S. cerevisiae Pox1p. Haploid strains with a disrupted allele were able to grow on fatty acids. The levels of acyl‐CoA oxidase activity in the ACO3 deleted strain, in an ACO1 deleted strain and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Using mutant strains disrupted for one or several pox genes enabled us to evaluate the activity of the different enzymes. Aox1 exhibits no detectable activity in the conditions we tested, Aox2 and Aox3 are longand short-chain specific, respectively and Aox4 and Aox5 exhibit a weak activity on a wide range of substrates [8]. We have observed in previous works the important role of the acyl-CoA oxidase in the pathway, Aox3 (short-chain specific) being responsible for continuation of oxidation after the C10 level [9] and for lactone reconsumption [10].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Using mutant strains disrupted for one or several pox genes enabled us to evaluate the activity of the different enzymes. Aox1 exhibits no detectable activity in the conditions we tested, Aox2 and Aox3 are longand short-chain specific, respectively and Aox4 and Aox5 exhibit a weak activity on a wide range of substrates [8]. We have observed in previous works the important role of the acyl-CoA oxidase in the pathway, Aox3 (short-chain specific) being responsible for continuation of oxidation after the C10 level [9] and for lactone reconsumption [10].…”
Section: Introductionmentioning
confidence: 58%
“…This shows that the metabolic pathway of the modified strain is altered by the disruption of several Aox encoding genes even if, in a previous study [8] we have shown that Aox2 (the remaining and long-chain specific enzyme) was very active. The low Aox activity in the mutant strain could result from the lack of several Aox important in the enzyme structure formation.…”
Section: Production Of Deca By the Optimized Strainmentioning
confidence: 70%
See 1 more Smart Citation
“…The strain used in this study is Y. lipolytica W29 MatA (ATCC 20460, CLIB89) or its derived mutant disrupted for genes coding for acyl-CoA oxidases (POX) [8]. To introduce the uracil auxotrophy into the mutant strain MTL37, the ura3-41 allele from the H222 ura3-41 strain [15] was introduced by transformation and selection of Ura− cells on YNB-5FOA medium as described previously [16] giving rise to strain MTLY40.…”
Section: Strain Constructionsmentioning
confidence: 99%
“…1) [1]. Y. lipolytica possesses a five-member family of acyl-CoA oxidases (Aox1p to 5 encoded by POX1 to 5), the enzymes catalysing the first step of ␤-oxidation, some of which are long-chain specific (Aox2p) [8] or short-chain specific (Aox3p) [9,10], the specificity resulting from only a small number of amino-acids (see Mlíčková et al in this volume, [11]). The short-chain spe-cific enzyme is involved in the degradation of the lactone ( Fig.…”
Section: Introductionmentioning
confidence: 99%